2022
DOI: 10.3390/ijerph19063603
|View full text |Cite
|
Sign up to set email alerts
|

Resilient Health and the Healthcare System. A Few Introductory Remarks in Times of the COVID-19 Pandemic

Abstract: People across the globe are facing increasingly complex public health emergencies that are responsible for the loss of life, economic and social problems with unprecedented damage and costs. For some sociologists, our society is even “a risk society” and our time is highly violative. Emergencies of different origin: stemming from natural environmental disasters, such as floods, hurricanes, intense drought, technical accidents, social unrest and last but not least—outbreaks of infectious diseases. This decade s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Three reviews contained lists of definitions from other studies 17 34 35. Another three reviews presented narrative collections and analyses of definitions 15 36 37…”
Section: Resultsmentioning
confidence: 99%
“…Three reviews contained lists of definitions from other studies 17 34 35. Another three reviews presented narrative collections and analyses of definitions 15 36 37…”
Section: Resultsmentioning
confidence: 99%
“…To deal with sudden disruptions and lack of knowledge during a pandemic with disastrous scales such as COVID-19, we need a resilient healthcare system that can: (1) ensure a comprehensive response considering health, social, and economic considerations simultaneously, (2) adjust capacity to meet patient demands, (3) preserve functions and resources to maintain routine and acute care, and (4) curb vulnerability to catastrophic losses in a community's economy and wellbeing [57] . To this end, Hanefeld et al [58] examined important aspects of health system resilience during the 2017 Ebola outbreak in Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For including emergency response team competency in SEDTC, we should focus attention on the resilience of individual team members. 24,25 A recent report showed that staff resilience plays an essential role in the development of overall patient safety. 26 As resilience of medical staffs can facilitate improvements in interprofessional teamwork, applications, safety climate development plays a central role in effective rapid response team function.…”
Section: N E E D For I Ncor Por Ati Ng R E Silie Nce Com Pete Ncie S ...mentioning
confidence: 99%
“…Although rapid response team performance is not uniform in each department, rapid response training in SEDTC should emphasize sedation‐related emergency and treatments. For including emergency response team competency in SEDTC, we should focus attention on the resilience of individual team members 24,25 …”
Section: Need For Incorporating Resilience Competencies In Sedtcmentioning
confidence: 99%